Pengaruh Product Assortment, Online Customer Review dan Price Discount terhadap Purchase Interest Pengguna Shopee di Kota Bandung - Mochamad Irfan Fauzie; Dedy Ansari Harahap; Mochamad Malik Akbar Rohandi (Bandung Conference Series: Business and Management, 2022)
Abstract. Information technology is growing rapidly, one of which is a online business, data obtained from Hootsuite & We Are Social (2021) states that 93% of Indonesian internet users, use the internet to search for products to buy, where 87.1% of them buy products online. this makes many entrepreneurs switch to online systems which gives rise to many competitors. Therefore, a strategy is needed to get consumer Interest Purchases including Product Assortment, Online Customer Reviews, and Price Discounts. This study was conducted to determine the effect of Product Assortment, Online Customer Reviews, and Price Discounts on Shopee Users' Purchase Interest. This study uses quantitative research methods with an associative analysis approach, which conducted on Shopee users in the city of Bandung with 320 Shopee users respondents. This research data uses primary data in the form of a questionnaire and the data analysis using multiple linear regression and hypothesis testing t-test for partial test and F-test for simultant test. The results of the study shows: Product Assortment had a significant and positive effect on Purchase Intention, Online Customer Reviews had a significant and positive effect on Purchase Intention, Price Discounts had a significant and positive effect on Purchase Intention, and Product Assortment, Online Customer Review and Price Discount together have a significant and positive effect on Purchase Interest. Keywords: Product Assortment, Online Customer Review, Price Discount, Purchase Interest. Abstrak. Perkembangan teknologi informasi kian berkembang pesat salah satunya bisnis daring, data yang didapat dari Hootsuite & We Are Social (2021) menyebutkan 93% pengguna internet Indonesia menggunakan internet untuk mencari produk dimana 87,1%-nya untuk membeli produk secara daring. hal ini membuat banyak pengusaha beralih ke sistem daring yang memunculkan persaingan ketat, maka dari itu dibutuhkan strategi untuk mendapatkan Purchase Interest konsumen diantaranya adalah dengan Product Assortment, Online Customer Review dan Price Discount. Penelitian ini dilakukan untuk dapat mengetahui pengaruh dari Product Assortment, Online Customer Review dan Price Discount terhadap Purchase Interest Pengguna Shopee. Penelitian ini menggunakan metode penelitian kuantitatif dengan pendekatan analisis asosiatif, yang dilakukan pada pengguna Shopee di kota Bandung dengan 320 responden pengguna Shopee. Data yang digunakan adalah data primer berupa kuesioner dengan analisis data menggunakan regresi linear berganda dan pengujian hipotesis secara parsial denga uji-t dan pengujian secara simultan dengan uji-F. Hasil dari penelitian yang dilakukan menunjukan Product Assortment berpengaruh positif dan signifikan terhadap Purchase Interest, Online Customer Review berpengaruh positif dan signifikan terhadap Purchase Interest, Price Discount berpengaruh positif adan signifikan terhadap Purchase Interest, dan Product Assortment, Online Customer Review dan Price Discount secara Bersama-sama berpengaruh positif dan signifikan terhadap Purchase Interest. Kata Kunci: Product Assortment, Online Customer Review, Price Discount, Purchase Interest